Emotion Regulation in Mindfulness-Based Interventions for Middle School Students: A Bibliometric Analysis - Hairani Lubis; Diah Rahayu (About the Journal, 2026)
Attention to the psychological well-being and academic achievement of high school students is increasing as the academic and emotional demands faced by students are high. Emotion regulation is seen as a key factor that affects learning adaptation, cognitive function, and academic achievement, so mindfulness emerges as a promising intervention in educational contexts. This study aims to systematically analyze the impact of mindfulness interventions on the regulation of emotions and academic achievement of high school students through a meta-analysis approach. The research method uses meta-analysis of experimental and quasi-experimental studies published in the 2010–2023 period, with the article selection process following the stages of identification, screening, and eligibility until 30 articles that meet the inclusion and methodological quality criteria are obtained. The results of the study showed that mindfulness interventions had a consistent positive effect on improving students' emotional regulation and improving academic achievement, both directly and through mediation mechanisms such as academic self-efficacy, academic buoyancy, mind-wandering reduction, and self-regulation. The findings also suggest that interventions implemented in a structured, sustainable manner, and supported by trained facilitators tend to produce stronger effects. The implications of this study confirm that the integration of evidence-based mindfulness interventions into the school environment has the potential to support the holistic development of students' emotional well-being and academic achievement, as well as the basis for the formulation of educational policies and practices that are more responsive to students' psychological needs.Perhatian terhadap kesejahteraan psikologis dan prestasi akademik siswa sekolah menengah atas semakin meningkat seiring dengan tingginya tuntutan akademik dan emosional yang mereka hadapi. Regulasi emosi dipandang sebagai faktor kunci yang memengaruhi adaptasi belajar, fungsi kognitif, dan pencapaian akademik, sehingga mindfulness muncul sebagai intervensi yang menjanjikan dalam konteks pendidikan. Penelitian ini bertujuan untuk menganalisis secara sistematis dampak intervensi mindfulness terhadap regulasi emosi dan prestasi akademik siswa melalui pendekatan meta-analisis terhadap studi eksperimental dan kuasi-eksperimental yang dipublikasikan pada periode 2010–2023. Proses seleksi artikel dilakukan melalui tahap identifikasi, penyaringan, dan kelayakan hingga diperoleh 30 artikel yang memenuhi kriteria inklusi dan kualitas metodologis. Hasil penelitian menunjukkan bahwa intervensi mindfulness memiliki efek positif yang konsisten dalam meningkatkan regulasi emosi dan prestasi akademik, baik secara langsung maupun melalui mekanisme mediasi seperti efikasi diri akademik, daya lenting akademik (academic buoyancy), pengurangan mind-wandering, dan regulasi diri. Temuan juga menunjukkan bahwa intervensi yang dilaksanakan secara terstruktur, berkelanjutan, serta didukung oleh fasilitator terlatih cenderung menghasilkan efek yang lebih kuat. Implikasi penelitian ini menegaskan bahwa integrasi intervensi mindfulness berbasis bukti ke dalam lingkungan sekolah berpotensi mendukung perkembangan holistik kesejahteraan emosional dan prestasi akademik siswa, sekaligus menjadi dasar dalam perumusan kebijakan dan praktik pendidikan yang lebih responsif terhadap kebutuhan psikologis siswa.